1998
DOI: 10.1002/hep.510270521
|View full text |Cite
|
Sign up to set email alerts
|

Chylomicrons alter the hepatic distribution and cellular response to endotoxin in rats

Abstract: Sepsis caused by gram-negative bacterial infection is an important and frequently devastating problem, annually affecting approximately 500,000 patients 1 and causing over 150,000 deaths. 2-6 While the incidence of sepsis has more than doubled during the last quarter century, 7 there has not been a substantial improvement in the survival rate since the 1970s. 8,9 Even though there are many effective antibiotics, they are often unsuccessful as the sole mode of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 72 publications
4
31
0
1
Order By: Relevance
“…The in vitro data mainly parallel those found in vivo. These data confirm that binding of LPS to lipoproteins decreases its ability to activate macrophages and endothelial cells (30,57,60,196,306,366,415,554,579) (Table 5). Recently, Grunfeld et al have shown a similar inhibitory effect of lipoprotein binding on LTA-induced activation of macrophages (177).…”
Section: Anti-inflammatory Rolesupporting
confidence: 78%
“…The in vitro data mainly parallel those found in vivo. These data confirm that binding of LPS to lipoproteins decreases its ability to activate macrophages and endothelial cells (30,57,60,196,306,366,415,554,579) (Table 5). Recently, Grunfeld et al have shown a similar inhibitory effect of lipoprotein binding on LTA-induced activation of macrophages (177).…”
Section: Anti-inflammatory Rolesupporting
confidence: 78%
“…Lors de chocs septiques, la LBP peut transférer les LPS aux lipoprotéines plasmatiques (HDL, chylomicrons), ce qui permet la neutralisation de l'activité des endotoxines (Eichbaum et al, 1991 ;Harris et al, 1993 ;Vreugdenhil et al, 2003). Cette neutralisation résulte de la liaison des lipoprotéines à leurs récepteurs notamment dans le foie, induisant ensuite l'élimination des LPS par sécrétion biliaire (Eichbaum et al, 1991 ;Harris et al, 1993Harris et al, , 1998Vreugdenhil et al, 2003). En plus de la LBP, la protéine de transfert des phospholipides (phospholipid transfer protein [PLTP]) peut lier les LPS et ainsi détoxifier l'organisme lors de chocs septiques (Gautier et al, 2008).…”
Section: Topical Issueunclassified
“…This neutralization results from the link of lipoproteins to their receptors notably in the liver, inducing LPS clearance with bile secretion (Eichbaum et al, 1991;Harris et al, 1993Harris et al, , 1998Vreugdenhil et al, 2003). Not only LBP but also the phospholipid transfer protein (PLTP) can bind LPS and contribute to detoxification during septic shocks (Gautier et al, 2008).…”
Section: Endotoxins Are Proinflammatory Moleculesmentioning
confidence: 99%